Principal-Agent in Implementing Village Funds in Linggo Village, Kejayan District, Pasuruan Regency - Aminullah, Aminullah (FIA UB, 2021)
The village fund is one of the many policy programs carried out by the government sourced from the state budget (APBN) which is allocated directly to the village. But in the implementation of the village fund, there are still problems so that in general the village fund is still not effective. This study analyzes the role of actors in the implementation of village funds from the perspective of the principal-agent whose locus is in Linggo village, Kejayan district, pasuruan regency. The focus in this study is the role of principal and agent in the stages of planning, implementation, and reporting of the village fund by measuring the effectiveness of implementation through the principles for cultivating effective implementation practice. Novelty of this research is to see the effectiveness of the implementation of the village fund from the perspective of the relationship of the principal agent. This study aims to create a model of the effectiveness of the village fund policy implementation in linggo village, kejayan district. The results showed that the relationship between the principal and agent must increase oversight so that the policy objectives can be achieved.